2023
DOI: 10.3390/polym15163413
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Class II MOD Cavities Restored by Direct and Indirect Techniques and Different Materials Combination

Vasiliki Tsertsidou,
Petros Mourouzis,
Dimitrios Dionysopoulos
et al.

Abstract: This study aimed to evaluate the fracture resistance of class II MOD cavities restored using different techniques and materials. Sixty extracted maxillary molars were selected and standardized class II MOD cavities were prepared using a custom-made paralleling device. The specimens were divided into four groups based on the restoration technique used: Group 1 (direct resin composite), Group 2 (short-fiber-reinforced composite resin), Group 3 (composite polyethylene fiber reinforcement), and Group 4 (CAD/CAM re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…There was no statistically significant difference in fracture resistance between direct and indirect restorations when composite is used for the restoration of posterior teeth (WMD: −7.09 [95%CI: −129.96, 145.76]; p = 0.16) (Figure 3). [24,26,27,29,31,40,42,45,47].…”
Section: Direct Vs Indirect Composite Resin Restorationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no statistically significant difference in fracture resistance between direct and indirect restorations when composite is used for the restoration of posterior teeth (WMD: −7.09 [95%CI: −129.96, 145.76]; p = 0.16) (Figure 3). [24,26,27,29,31,40,42,45,47].…”
Section: Direct Vs Indirect Composite Resin Restorationsmentioning
confidence: 99%
“…There was no statistically significant difference in fracture resistance between direct composite and indirect ceramic restorations (WMD: 18.87 [−212.04, 249.78]; p = 0.87) (Figure 4). [24,26,27,29,31,40,42,45,47].…”
Section: Direct Composite Resin Vs Indirect Ceramic Restorationsmentioning
confidence: 99%
“…However, due to their physical limitations, clinical failure may occur in the case of extensive restorations. The two most concerning problems with conventional particulate filler composites (PFCs) are polymerization shrinkage [ 11 , 12 , 13 , 14 ] and that—even though they are brittle, strong materials—they lack fracture toughness [ 15 ]. The problem of low fracture toughness is particularly evident in larger direct restorations, as the volume of the material increases.…”
Section: Introductionmentioning
confidence: 99%
“…Short-fiber-reinforced composite (SFRC) materials seem to offer a solution to this problem, as these materials are much closer to dentine in terms of their physical parameters [ 16 ]. In previous studies, it has been shown that even deep MOD cavities can be reinforced by the application of SFRCs in direct restorations [ 15 , 20 ]. Due to this reinforcing effect, in recent years, numerous innovative restoration techniques and materials have appeared.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation